1998
DOI: 10.1074/jbc.273.3.1647
|View full text |Cite
|
Sign up to set email alerts
|

A High Affinity Glutamate/Aspartate Transport System in Pancreatic Islets of Langerhans Modulates Glucose-stimulated Insulin Secretion

Abstract: To examine the role of glutamatergic signaling in the function of pancreatic islets, we have characterized a high affinity glutamate/aspartate uptake system in this tissue. The islet [3 H]glutamate uptake activity was Na ؉ -dependent, and it was blocked by L-trans-pyrrolidine-2,4-dicarboxylic acid, a blocker of neuronal and glial glutamate transporters. Islet glutamate transport activity exhibited a V max of 8.48 ؎ 1.47 fmol/min/islet (n ‫؍‬ 4), which corresponds to 102.2 ؎ 17.7 pmol/min/mg islet protein. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 31 publications
2
28
1
Order By: Relevance
“…Several works have reported that L-glutamate or agonists of glutamate receptor stimulate to some extent the secretion of insulin under high glucose conditions in cultured cells, isolated islets, and perfused pancreas (4,6,7,9). Consistently, we observed that L-glutamate slightly stimulates (ϳ10%) insulin secretion from MIN6 m9 cells (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Several works have reported that L-glutamate or agonists of glutamate receptor stimulate to some extent the secretion of insulin under high glucose conditions in cultured cells, isolated islets, and perfused pancreas (4,6,7,9). Consistently, we observed that L-glutamate slightly stimulates (ϳ10%) insulin secretion from MIN6 m9 cells (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Another significant finding obtained in the present study is that the L-glutamate signaling triggers GABAergic response in clonal ␤ cells and isolated islets. The released L-glutamate may bind to the corresponding receptors on the islet cells, causing a paracrine or autocrine response (3)(4)(5)(6)(7)(8)(9)(10)(11). Islet ␤ cells contain GABA in SLMVs at concentrations comparable level to the central nervous systems (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…A glutamate uptake activity has been described in pancreatic islets, and a high affinity glutamate/aspartate transporter has been cloned from the human pancreas (24,25); however, its precise identity and physiological role have not been characterized. In the present study, we demonstrate that ␤-cells are selectively vulnerable to glutamate-induced toxicity and that GLT1 is present and functional in the islet where it influences glucagon release and promotes ␤-cell survival.…”
mentioning
confidence: 99%
“…Our data and theoretical consideration suggest that KYNA or its metabolic precursor L-kynurenine may be of therapeutic value in heatstroke syndromes. However, the use of KYNA as a neuroprotective agent can be excluded because it is barely able to cross the BBB, whereas L-kynurenine is transported much more readily across the BBB [34] .…”
Section: Discussionmentioning
confidence: 99%